Comparison of the effectiveness of self-instructional materials and didactic lecture in learning physiology - Ibañez, Leticia T. (2000)
This study was undertaken to compare the effectiveness and acceptability of the use of self-instructional materials (SIM) over the traditional lecture approach in learning Gastrointestinal Physiology. Two modules were utilized by 160 Year level III medical students for learning GI Physiology. Comparison of acceptability of the modular versus the lecture method was done using a questionnaire. Learning was determined by incremental change of score comparing pre-test results. Both teaching methods produced an incremental change of about 40-50%. The lecture method was preferred by students for making learning objectives clear, for making them understand the subject, for better recall and for preparing them for the exams making the modular approach more acceptable. About fifty percent (49.6%) of students preferred the modular approach, thirty nine (39.5%) preferred a combination of modular and lecture methods, while only ten percent (10.9%) preferred the lecture method. Since many students chose the combined teaching methods, it may be in their best interest to make both modular and lecture methods available so that learning can be maximized.